Integrating the Urea-to-Creatinine Ratio with Clinical Variables to Improve Etiological Discrimination in Acute Kidney Injury - Luca Malatesta; Marco Allinovi; Sofia Brucia; Mariapia Carafa; Sara Dal Lago; Glenda Cancila; Alberto Parise; Chiara Giannini; Francesco Peyronel (Journal of Clinical Medicine, 2026)
Background: The urea-to-creatinine ratio (UCR) is used to support the differential diagnosis of acute kidney injury (AKI); however, its diagnostic utility remains debated. We explored the clinical relevance of UCR in the initial etiological assessment of AKI, also considering relevant clinical modifiers. Methods: We retrospectively analyzed 590 hospitalized patients classified as pre-renal (n = 319), parenchymal (n = 135), or post-renal (n = 136) AKI. UCR was compared across AKI subtypes and stratified by pre-existing chronic kidney disease (CKD). Logistic regression models assessed the association between UCR and pre-renal AKI, excluding post-renal cases. Diagnostic performance was evaluated using receiver operating characteristic curve analysis. An exploratory analysis was performed within parenchymal AKI according to histopathological patterns and the presence of nephrotic syndrome. Results: Baseline characteristics differed across AKI subtypes, including age, sex, and CKD. UCR was higher in pre-renal than in parenchymal and post-renal AKI (p < 0.001), despite substantial overlap. Stratification by CKD did not reveal differences within AKI subtypes; however, in pre-renal AKI, UCR decreased progressively with advancing CKD stage (p < 0.001). UCR was significantly associated with pre-renal AKI, and diagnostic performance improved when combined with age and advanced CKD. Within parenchymal AKI, higher UCR values were observed in glomerular disease, particularly with nephrotic syndrome. Conclusions: UCR varies across AKI etiologies and is influenced by age and baseline kidney function. Although its standalone diagnostic performance is limited, integration with simple clinical variables improves discrimination between pre-renal and parenchymal AKI, supporting its use as a complementary tool in early AKI evaluation while emphasizing the need for comprehensive clinical assessment.